The Effect of Resistance Training on Cardiorespiratory Fitness on Healthy Male in Surabaya - Ramadhan, Muhammad Qashmal; Irwadi, Irfiansyah; Eko Putranto, Johanes Nugroho (Faculty of Medicine, Universitas Airlangga, 2025)
Introduction: Low fitness levels have long been the cause of various diseases that are often experienced by humans. Although the process of a disease is something that is related to many factors, it cannot be denied that lack of physical fitness is one of the biggest factors. In theory, the results of the VO2Max test will increase due to several mechanisms including increased respiratory muscle strength and increased cardiac output. Aim: Based on this theory, this study was conducted to see the impact of resistance training on cardiorespiratory fitness. Method: This study used a Quasi-Experiment design with a pre-post test with a total sample of 16 people and was divided into 2 treatment and control groups. Treatment is the group that is given a resistance training regimen and control is the group that is not given. Data was obtained by testing the YMCA Ergometry Cycle Test, then processed with SPSS with the Shapiro-Wilk test and Levene test and then a paired t-test was carried out. Results: The results of this study indicate the effect of providing resistance training with a p value = 0.01 which shows significant results. Conclusion: Resistance training increases cardiorespiratory fitness with quite significant results and can improve fitness, but it is still recommended for each individual to balance this resistance training with endurance training for optimal body fitness.